Study of mouthguard design for endurance and air-flow enhancement - Ilmin, Siti Syazwani (2015)
Recently, mouthguard is one of the important device to the athletes during sports and exercise. Wearing a mouthguard is a must to prevent them from any orofacial injuries occurs during their sport activities. Therefore, to make sure it is safe and comfort, a study on the mouthguard design is carried out to investigate the performance of the mouthguards, in term of stress distribution and air flow path by improving the pressure difference between the ambient (outside) and the oral cavity pressure (inside). A preliminary design has been study to simulate its total deformation and stress, in terms of Von Mises Stress by using ANSYS 15.0 Workbench. From the results, the critical parts are identified on the preliminary design and later being used to improve the design to the new one. By increasing the thickness of the preliminary design, the total deformation has been decreased for about 0.2 mm to 0.16 mm for the exerted forces of 50 N to 500 N for external forces comes from outside, whereas, for internal forces from 100 N to 600 N has decreased about 0.24 mm to 1.44 mm. The simulation process is then followed by the air flow study in the oral cavity with the open mouth about 0.5 mm when the athlete is doing the exercise with 4.43 m/s speed of flowing air entering the mouth. The finding indicates that the modified mouthguard has large value of velocity streamline compared with the preliminary design because it is thicker than the first design. The difference pressure between both of the designs are, 140.09 Pa for the preliminary design and 401.86 Pa for the modified design. Velocity stream line also showed that higher speeds occur in the near mouth guards, that is, between the bottom surfaces of the mouthguard and the lower teeth. The results show that, the thicker the mouthguard design, the better it is for prevention but less in air flow distribution into the oral cavity.